An analysis of the role of firearms control laws in South African society - Zazeraj, Victor John (Department of Sociology, 2015)
This study had as its purpose an attempt to establish on empirical grounds the role firearms control laws play in South African society. A holist methodological position was adopted from among the alternatives available for scientific social research, and the structural-functional theoretical framework of the main line tradition was employed for the purposes of the analysis. Accordingly, legislation was defined as serving a primarily integrative function in society, (integration being functionally one of four system imperatives), by translating prevailing values and norms into a stable, attributive code. A discussion of general historical and contemporary perspectives related to purpose(s), role, and efficacy of restrictive firearms legislation preceded a survey of the development of gun controls in the Republic of South Africa. Current legislative provisions in this context were then dealt with in some detail. Research into the official documentary reports of the S.A. Department of Statistics (i.e., the Report on Deaths, and Statistics of Offences), and the Annual Report of the Commissioner of the South African Pol ice, covering a period of years, was carried out and although some of the required statistical information was inadequate, or entirely non-existent, it was finally concluded on the basis of available evidence that such legislation is enacted in this society on the assumption that it serves the purposes of crime reduction and civil peace. This assumption was shown to be empirically unsupported, and an alternative approach was called for in terms of which legislators should place greater positive emphasis on the individual right to keep and bear arms. It was concluded that such a shift of emphasis would more effectively promote the defined role of legislation in South African society.